2021
DOI: 10.1172/jci.insight.143811
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of AMPK minimizes graft-versus-host disease through an early impact on effector donor T cells

Abstract: Study approval. All animal studies were approved and carried out according to Institutional Animal Care and Use Committee guidelines from the University of Pittsburgh. All studies on human cells were designated exempt status by the University of Pittsburgh Institutional Review Board. Author contributionsDAM, KJB, and PC designed and performed experiments, analyzed data, and reviewed the manuscript. KP designed and performed experiments and analyzed data. NJM, AKD, and RAB performed experiments and analyzed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…In vivo metformin administration increased the ratio of Treg/ Th17, enhanced autophagy and reduced mTOR/STAT3 signaling (59) resulting in the amelioration of murine aGVHD severity (59). In contrast, a recent study reported that the loss of AMPK in donor T cells attenuated aGVHD (60), suggesting a pAMPK independent mechanism of GVHD amelioration by metformin (60). Allogeneic murine and human T cells upregulated pAMPK during early aGVHD and xenogeneic GVHD respectively.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…In vivo metformin administration increased the ratio of Treg/ Th17, enhanced autophagy and reduced mTOR/STAT3 signaling (59) resulting in the amelioration of murine aGVHD severity (59). In contrast, a recent study reported that the loss of AMPK in donor T cells attenuated aGVHD (60), suggesting a pAMPK independent mechanism of GVHD amelioration by metformin (60). Allogeneic murine and human T cells upregulated pAMPK during early aGVHD and xenogeneic GVHD respectively.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…The investigators established AMPK double knockout (AMPK-dKO) mice lacking AMPKa1 and AMPKa2 in all peripheral T-cells. AMPK is a heterotrimeric molecule with the a subunit as kinase domain and the b/g subunits being important for stability and substrate specificity (175,(178)(179)(180). Although T-cell development and in vitro proliferation in a MLR was not different between AMPK-dKO and WT T-cells, AMPK-deficient T-cells caused less severe GvHD after transplantation into lethally irradiated recipient mice.…”
Section: Amp Kinase (Ampk)mentioning
confidence: 99%
“…Co-transplantation experiments revealed that AMPK-dKO T-cells stimulated an increase of WT Tregs. Given the importance of Tregs to reduce GvHD severity, increased Treg numbers due to accompanying AMPK-dKO cells were named as a major mechanism to suppress GvHD severity (175,(182)(183)(184). Although there are no AMPK inhibitors available yet, inhibition of AMPK in T-cells could serve as novel target for GvHD treatment; however, more detailed analysis is needed to better understand the role of AMPK after allo-HCT (175).…”
Section: Amp Kinase (Ampk)mentioning
confidence: 99%
See 2 more Smart Citations